Non-invasive physical plasma for preventing radiation dermatitis in breast cancer: study protocol for a phase 3 randomised double-blind placebo-controlled trial (NIPP-RD III) - Cas Stefaan Dejonckheere; Julian Philipp Layer; Gustavo Renato Sarria; Shari Wiegreffe; Andrea Renate Glasmacher; Younèss Nour; Davide Scafa; Thomas Müdder; Teresa Anzböck; Frank Anton Giordano; Matthias Bernhard Stope; Leonard Christopher Schmeel; et al. (Trials)
Abstract Background Radiation dermatitis (RD) is the most common side effect of breast irradiation, yet only few potent preventative and therapeutic options are available. Following encouraging results from a phase 1 and 2 trial on the topical use of non-invasive physical plasma (NIPP), a very well-tolerated physical treatment option to promote tissue regeneration generated from ambient air, we now present the study protocol for a planned phase 3 trial. Methods In this randomised double-blind placebo-controlled trial, patients with breast cancer will be randomised (1:1) to receive either 120 s of NIPP or sham treatment with an identical device daily during hypofractionated breast irradiation following breast-conserving surgery. Standard skin care with urea lotion will be applied twice daily to the whole breast by all patients. Acute skin toxicity will be assessed weekly and includes clinician- (CTCAE v5.0) and patient-reported (modified RISRAS), and objective (spectrophotometry) assessments. The trial has started enrolment in the first quarter of 2024 and is projected to recruit 140 patients over 36 months. Discussion This randomised controlled trial will recruit a homogeneous patient collective in terms of RD risk and aims to unequivocally establish the impact of NIPP on RD by employing a robust trial design, incorporating both the patient’s perspective and validated objective outcome measures. If the addition of NIPP proves useful, it might reduce both physical and psychological distress caused by RD in numerous breast cancer patients and beyond. Trial registration German Clinical Trial Registry DRKS00032560 (January 9th 2024).